Beneficiation of Hard Rock Lithium Ore and the Effect of Calcination - Nazir, Muhammad Kashif (Curtin University, 2022)
Calcination is a compulsory pre-treatment during the processing of spodumene ores that transforms a-phase of spodumene to ß-phase that is more reactive. This conversion happens at high temperatures above 900 °C. The resultant ß-spodumene has highly altered physical properties with 30% more volume than that of a-spodumene. ß-spodumene is more reactive towards chemical reagents and mechanical treatments due to more open crystal structure. This may result in higher Li grades and recoveries.